A taxonomy of secure data aggregation in wireless sensor networks. (1st January 2012) - Alzaid, Hani; Foo, Ernest; Nieto, Juan Manuel González; Park, DongGook
Recent advances in wireless sensor networks (WSNs) have led to several new promising applications including habitat monitoring and target tracking. However, data communication between nodes consumes a large portion of the entire energy consumption of the WSNs. Consequently, data aggregation techniques can significantly help to reduce the energy consumption by eliminating redundant data travelling back to the base station. The security issues such as data integrity, confidentiality, and freshness in data aggregation become crucial when the WSN is deployed in a remote or hostile environment where sensors are prone to node failures and compromises. There is currently research potential in securing data aggregation in WSNs. With this in mind, the security issues in data aggregation for the WSN will be discussed in this article. After that, the 'state-of-the-art' in secure data aggregation schemes will be surveyed and then classified into two categories based on the number of aggregator nodes and the existence of the verification phase.